Phylogeography of the genus Podococcus (Palmae/Arecaceae) in Central African rain forests: Climate stability predicts unique genetic diversity - (:unkn) unknown (My University, 2016)
The tropical rain forests of Central Africa contain high levels of species diversity. Paleovegetation or biodiversity patterns suggested successive contraction/expansion phases on this rain forest cover during the last glacial maximum (LGM). Consequently, the hypothesis of the existence of refugia e.g. habitat stability that harbored populations during adverse climatic periods has been proposed. Understory species are tightly associated to forest cover and consequently are ideal markers of forest dynamics. Here, we used two central African rain forest understory species of the palm genus, Podococcus, to assess the role of past climate variation on their distribution and genetic diversity. Species distribution modeling in the present and at the LGM was used to estimate areas of climatic stability. Genetic diversity and phylogeography were estimated by sequencing near complete plastomes for over 120 individuals. Areas of climatic stability were mainly located in mountainous areas like the Monts de Cristal and Monts Doudou in Gabon, but also lowland coastal forests in southeast Cameroon and northeast Gabon. Genetic diversity analyses shows a clear North-South structure of genetic diversity within one species. This divide was estimated to have originated some 500,000years ago. We show that, in Central Africa, high and unique genetic diversity is strongly correlated with inferred areas of climatic stability since the LGM. Our results further highlight the importance of coastal lowland rain forests in Central Africa as harboring not only high species diversity but also important high levels of unique genetic diversity. In the context of strong human pressure on coastal land use and destruction, such unique diversity hotspots need to be considered in future conservation planning.
Keywords: African Research